Program Components and Outcomes of Individuals With Dementia: Results From the Replication of an Evidence-Based Program. (May 2017) - Menne, Heather L.; Bass, David M.; Johnson, Justin D.; Kearney, Keith R.; Bollin, Salli; Teri, Linda
This study examines whether the delivery of three components, (a) exercise training, (b) behavior management skill building, and (c) dementia-related education, in an evidence-based program are differentially associated with changes in outcomes for individuals with dementia (IWDs) after 3 months. Data come from 508 IWDs participating in the community replication of the evidence-based "Reducing Disability in Alzheimer's Disease" program. Regression results indicate that after 3 months, more exercise sessions are associated with improvements in physical functioning, mobility, minutes exercising, and symptoms of depression; more dementia education sessions are related to fewer restricted activity days; and more behavior management sessions are related to more symptoms of depression. As resource-strapped agencies look to best serve participants, further analysis and consideration is needed to determine the ideal balance of program efficacy, feasibility, and resources, as well as program benefits for IWDs and caregivers.